The Effect of Competency, Negotiation Model and Emotional Intelligence in the Stakeholders Capability on Result of Negotiation Construction Dispute in Indonesia - Ladika, Ladika; Syafwandi, Syafwandi; Susetyo, Budi (International Review of Management and Marketing, 2020)
The construction project is a series of activities that are long, complex and increase potential of construction understanding differences, disagreements, and conflicts between various parties involved in construction work. So many construction projects that cause disputes between parties. In negotiating disputes, negotiations often take place; the negotiation process requires the capability to get the best results, such as competency, negotiation model and emotional intelligence. This research based on 102 samples of respondents from 10 constrution project in Indonesia among 5 highrise building projects and 5 industrial projects. Subject of research focused on the four stakeholders in the main project, which will be analyzed with the partial structural-least square equation model (PLS-SEM). The results of the analysis show that competency and emotional intelligence have significant positive effects to negotiations result in construction dispute. Negotiation model does not influence the negotiation results in the highrise building projects or industrial projects. But the results were different if the negotiation model that was added with the competency would have an significant positive effects to negotiations result in construction dispute. Keywords: Negotiation, Competency, Emotional Intellegence, Construction, Dispute JEL Classifications: D91, L74, O22, J53 DOI: https://doi.org/10.32479/irmm.9651